" Methods of Teaching English in Non-Philology Educational Institutions " (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The demand for English proficiency in non-philology educational institutions is increasing globally, driven by the language's status as the lingua franca of science, technology, and international business. This article explores effective methods for teaching English in non-philology settings, highlighting the integration of language skills into specialized curricula, the use of technology-enhanced learning tools, and the adaptation of teaching methodologies to suit diverse learning styles and professional needs. The findings suggest that a contextualized, learnercentered approach significantly enhances English language acquisition among students in non-philology fields.